Chromatic dispersion measurement using optical beating null frequency - Abdul Rashid, Hairul Azhar; Mokhtar, Mohd Ridzuan; Yusoff, Zulfadzli; Gopinathan, Vinesh; Al-Qdah, Malik T.; A. Rahman, Faidz (SPIE Digital Library, 2008)
A new technique for measuring the accumulated chromatic dispersion in single-mode fibers is presented. The proposed simple and tunable technique uses the null frequency of the optical beating signal between pump, probe, and four-wave-mixing conjugated signals as the pump and probe frequency separation is changed. The null frequency of the optical beating signals varies with the accumulated chromatic dispersion in the single mode fiber. A full mathematical model of the measurement technique is developed and is supported by experimental results. The technique is successfully demonstrated experimentally using a semiconductor optical amplifier as a phase conjugator to achieve a null frequency variation of 1.2 GHz for a difference of 960-ps/nm accumulated chromatic dispersion. (C) 2008 society of Photo-Optical Instrumentation Engineers.